2022
DOI: 10.3389/fsurg.2022.963231
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the development of bone starvation syndrome after total parathyroidectomy in patients with renal hyperparathyroidism

Abstract: PurposeTo investigate the factors affecting the development of bone starvation syndrome (HBS) after total parathyroidectomy in patients with renal hyperparathyroidism (SHPT).Patients and methodsThe clinical data and perioperative indices of 141 patients who underwent PTX for SHPT were retrospectively analyzed. The patients were divided into HBS and non-HBS groups based on postoperative minimum blood calcium <1.87 mmol/L. The differences in general clinical data and perioperative related indices between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For instance, we mention a single-center, retrospective study on 141 individuals with RHPT that identified a HBS prevalence of 32% (N1 = 46) following successful PTx with at least 3 parathyroid glands being auto-transplanted. Pre-operative predictors of HBS (univariate analysis) were: higher dialysis age, respectively, increased values of PTH, calcitonin, and AP (which was found to be an independent predictor of HBS; a cutoff of 199.5 U/L offering a sensitivity of 80.85%, and a specificity of 82.61% regarding post-operatory HBS prediction), while pre-surgery PTH was correlated with the duration of intravenous regime of calcium replacement and total calcium dose (via intravenous supplementation) amid HBS [104].…”
Section: Pre-operatory Hbs Predictors In Subjects With Rphtmentioning
confidence: 88%
See 4 more Smart Citations
“…For instance, we mention a single-center, retrospective study on 141 individuals with RHPT that identified a HBS prevalence of 32% (N1 = 46) following successful PTx with at least 3 parathyroid glands being auto-transplanted. Pre-operative predictors of HBS (univariate analysis) were: higher dialysis age, respectively, increased values of PTH, calcitonin, and AP (which was found to be an independent predictor of HBS; a cutoff of 199.5 U/L offering a sensitivity of 80.85%, and a specificity of 82.61% regarding post-operatory HBS prediction), while pre-surgery PTH was correlated with the duration of intravenous regime of calcium replacement and total calcium dose (via intravenous supplementation) amid HBS [104].…”
Section: Pre-operatory Hbs Predictors In Subjects With Rphtmentioning
confidence: 88%
“…An amount of 23 studies were retrospective and 4 were of prospective, prospective-retrospective type, respectively, longitudinal and a national database cohort. Considering the number of enrolled participants per study, 12 studies included less than 100 participants per study, as follows: 19 (n = 2), 35, 37 (n = 2), 41, 45, 53, 62, 77, 79, 84; 9 studies enrolled between 100 and 200 individuals per study (of 108, 115, 120, 130, 131, 141, 148, 167, and 196), 3 studies had between 200 and 300 patients per study (specifically, 252, 260, and 297) while 3 larger studies had more than 700 patients per study (N = 796, 1846, and 7171), regardless the study design, a total of 12,468 patients with RHPT [1,4,17,30,40,84,85,[104][105][106][107][108][109][110]112,116,117,[123][124][125][126][127][128][129][130][131][132] (Table 5).…”
Section: Post-operatory Findings In Rhpt: Focus On Hbsmentioning
confidence: 99%
See 3 more Smart Citations